Effectiveness in Retrieving Legal Precedents - Mentzingen, Hugo (2025)
Mentzingen, H., António, N., & Bação, F. (2025). Effectiveness in Retrieving Legal Precedents: Exploring Text Summarization and Cutting-Edge Language Models Toward a Cost-Efficient Approach. Artificial Intelligence and Law. https://doi.org/10.1007/s10506-025-09440-2 --- The authors acknowledge Brazil's Superintendency of Private Insurance for supporting and providing data for this work. This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS) (https://doi.org/10.54499/UIDB/04152/2020).